"Procesos administrativos en extractora de palma aceitera del cantón Quevedo y su incidencia en los costos de producción, período 2001-2012, Plan de gestión". - Guanín Porras, Edwin Marcelo (2013)
This research considers the company as part of a society that has an impact and responsibility for their actions, creating an apparent conflict between profit and social responsibility. The administrative process is the activity that the administrator must perform to develop human resources, technical, material and financial resources are there in the company. At present, the administrative processes for oil extraction becomes a very complex activity, although this process has an operational dimension, requires a qualitative process to order all the items, in order to strengthen the most significant well organization such as the quality of its management. In research methods were applied deductive inductive; hypothetical - deductive and descriptive, explanatory and scientific observation was made through perception directed toward the object of study in its natural conditions, from previously established objectives by consistent use of scientific means. Among the strategies used to obtain information were used: Observation tours through companies in order to perceive the reality of the situation of the extractors. Guided Survey managers of the extractors. Survey applied to farmers who sell their produce to the extractors in research. From the results obtained and discussed general hypothesis is accepted: "The efficiency of the administrative process in palm oil extraction affects the optimization of production costs." As a general conclusion it can be said that among the indicators of Production Management, Market, Offer, Competition and an important factor for improvement are the incentives that project quality within the organization, as well as have policies, procedures and methods of performance it must become a mainstay in the control of the proposed indicators. Finally, we suggest as a proposal: Management Plan for the Improvement of the marketing of oil extraction oil palm Quevedo area. Keywords: Oil palm, extractor, management plan